Gone To The Market? The Development of Asian and Greek-Cypriot Community Media in Britain - Tsagarousianou, Roza (Javnost-The Public, 1999)
This article focuses on minority community media (ethnic minority radio, cable, satellite and terrestrial television) in the UK and their position within global diasporic media landscapes as well as in the media landscape of contemporary Britain. These media, partly products of the end of frequency scarcity which has led to media market fragmentation and encouraged/enabled the creation of new, specialised media, are distinct from other local, regional or community media as they identify their audience in minority communities whose identities are not rooted in well bounded localities. Drawing upon research on Asian and Greek-Cypriot community media in the UK, the article attempts to chart and discuss critically the development of ethnic community media in the UK over the past two decades. It examines the provision of programming for ethnic communities within the framework of Public Service Broadcasting and assesses the record of the main terrestrial channels in this area. It then assesses the community politics and the political, legal and regulatory framework which have led to the emergence of ethnic community-specific electronic media (cable and satellite television, radio and, more recently, terrestrial television).